Robust multiperiod poverty comparisons - Johannes Gräb; Michael Grimm (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
We propose a new methodology for comparing poverty over multiple periods across time and space that does not arbitrarily aggregate income over various years or rely on arbitrarily specified poverty lines or poverty indices. Following Duclos et al. (2006a), we use the multivariate stochastic dominance methodology to create dominance surfaces for different time spans. We elaborate the method first for the bidimensional case, using as dimensions income observed over two periods: one at the beginning and one at the end of a time span. Subsequently, we extend it to the case where incomes are observed over n-periods. We illustrate our approach by performing poverty comparisons using data for Indonesia and Peru.
Keywords: 330; Multiperiod Poverty; Poverty Dominance; Poverty Dynamics; Chronic Poverty.; Armut; Disparitätsmaß; Soziale Mobilität; Vergleich; Multivariate Analyse; Theorie; Indonesien; Peru